(untitled) - Green, Jocelyn (Thorndike, Maine, 2016)
"Richmond, Virginia, 1863. Compelled to atone for the sins of her slaveholding father, Union loyalist Sophie Kent risks everything to help end the war from within the Confederate capital and abolish slavery forever"--
Includes bibliographical references.
Keywords: Large type books; Virginia; Ficiton; Virginia; Fiction; Abolitionists; Slaves; United States; Fiction; History; Civil War, 1861-1865; Historical fiction; Spy stories; Christian fiction